Pembelajaran Daring Pada Mata Pelajaran Pendidikan Agama Islam di SDIT Syarif Ar-Rasyid Islamic School Medan Tahun Ajaran 2020-2021 - Reza Noprial Lubis (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2022)
This study uses qualitative research with descriptive methods, which are based on the focus to reveal that qualitative research is about various events that occur in the hope of obtaining real data and truly describing the actual situation in the object under study. SDIT Syarif Ar-Rasyid Islamic School is an institution located at Menteng Street 7 Number 186, Medan Denai District, Medan City. The results are based on research and discussion, so the key is that the preparation of PAI teachers in carrying out learning is quite challenging. This can be seen from the document prepared by the teacher, namely the planned mode learning implementation plan. Barriers to daring learning in PAI Subjects at SDIT Syarif Ar-Rasyid Islamic School, namely: (1) Students are still classified as children, so using online learning applications requires parental guidance. This has an impact on the absence of students, where learning activities are gathered together with the activities of parents; (2) There is no learning support media that is considered effective for carrying out bold learning activities. Thus, PAI learning is only carried out through the WhatsApp Video Call application.